Cellular senescence in cancer: from mechanism paradoxes to precision therapeutics - Tiejun Feng; Fuda Xie; Leo M.Y. Lee; Zhiqiang Lin; Yifan Tu; Yang Lyu; Peiyao Yu; Jialin Wu; Bonan Chen; Ge Zhang; Gary M.K. Tse; Ka Fai To; et al. (Molecular Cancer)
Abstract Cellular senescence is a double-edged sword in cancer biology, functioning as both a tumor-suppressive mechanism and a driver of malignancy. Initially, senescence acts as a protective barrier by arresting the proliferation of damaged or oncogene-expressing cells via pathways such as oncogene-induced senescence and the DNA damage response. However, persistent senescence-associated secretory phenotype and metabolic reprogramming in senescent cells create a pro-inflammatory, immunosuppressive tumor microenvironment, fueling cancer progression, therapy resistance, and metastasis. This comprehensive review systematically examines the molecular mechanisms of senescence across diverse cancers, spanning digestive, reproductive, urinary, respiratory, nervous, hematologic, endocrine, and integumentary systems, and elucidates its context-dependent roles in tumor suppression and promotion. We highlight groundbreaking therapeutic innovations, including precision senolytics, senomorphics, and combinatorial strategies integrating immunotherapy, metabolic interventions, and epigenetic modulators. The review also addresses microenvironment remodeling and cutting-edge technologies for dissecting senescence heterogeneity, epigenetic clocks for biological age prediction, and microbiome engineering to modulate senescence. Despite their promise, challenges such as off-target effects, biomarker limitations, and cellular heterogeneity underscore the need for precision medicine approaches. Finally, we propose future directions to harness senescence as a dynamic therapeutic target, offering transformative potential for cancer treatment.